Taming the SARS-CoV-2-mediated proinflammatory response with BromAc® - Ferreira, Geovane Marques; Clarindo, Felipe Alves; Ribeiro, Ágata Lopes; Gomes-de-Pontes, Letícia; de Carvalho, Luciana Debortoli; Martins-Filho, Olindo Assis; da Fonseca, Flávio Guimarães; Teixeira, Mauro Martins; Sabino, Adriano de Paula; Eapen, Mathew Suji; Morris, David L.; Valle, Sarah J.; et al. (Frontiers in Immunology, 2023)
In the present study, the impact of BromAc®, a specific combination of Bromelain and Acetylcysteine, on the SARS-CoV-2-specific inflammatory response was evaluated. BromAc® demonstrated robust anti-inflammatory activity in human peripheral blood cells upon SARS-CoV-2 viral stimuli, reducing the cytokine storm, composed of chemokines, growth factors, proinflammatory and regulatory cytokines produced after short-term in vitro culture with the inactivated virus (iSARS-CoV-2). A combined reduction in endothelial growth factor-VEGF induced by SARS-CoV-2, in addition to steady-state levels of platelet recruitment-associated growth factor-PDGF-bb was observed, indicating that BromAc® may be important to reduce thromboembolism in COVID-19. The immunophenotypic analysis of the impact of BromAc® on leukocytes upon viral stimuli shows that BromAc® was able to downmodulate the populations of CD16+ neutrophils and CD14+ monocytes observed after stimulation with iSARS-CoV-2. Conversely, BromAc® treatment increased steady state HLA-DR expression in CD14+ monocytes and preserved this activation marker in this subset upon iSARS-CoV-2 stimuli, indicating improved monocyte activation upon BromAc® treatment. Additionally, BromAc® downmodulated the iSARS-CoV-2-induced production of TNF-α by the CD19+ B-cells. System biology approaches, utilizing comprehensive correlation matrices and networks show distinct patterns of connectivity in groups treated with BromAc®, suggesting loss of connections promoted by the compound and by iSARS-CoV-2 stimuli. Negative correlations amongst proinflammatory axis and other soluble and cellular factors are observed in iSARS-CoV-2 group treated with BromAc® as compared to untreated, demonstrating that BromAc® is disengaging proinflammatory responses and their interactions with other soluble factors and axis orchestrated by SARS-CoV-2. These results give new insights on the mechanisms for the robust anti-inflammatory effect of BromAc® in the steady state as well SARS-CoV-2-specific immune leukocyte responses, indicating its potential as a therapeutic strategy for COVID-19.